2019
DOI: 10.1016/j.joco.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of color vision deficiency in the northeast of Iran

Abstract: Purpose To determine the prevalence of color vision deficiency (CVD) in the northeast of Iran. Methods This cross-sectional, population-based study was conducted in Mashhad, in the northeast of Iran. Multistage cluster sampling was used for selecting the participants. After preliminary screening, the subjects underwent a complete ophthalmic examination. The examination included the measurement of visual acuity, refraction, and slit-lamp biomicroscopy. The Farnsworth D-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
1
15
4
3
Order By: Relevance
“…Additional future work includes investigating the effects of other variations in colour perception. Even among those with regular colour vision, variations in colour perception exist [22], including demographical trends [21,28]. Moreover, monochromacy was not discussed in this work because of its rarity [24] but likely has an even more pronounced effect on colour discriminability than the deficiencies investigated here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional future work includes investigating the effects of other variations in colour perception. Even among those with regular colour vision, variations in colour perception exist [22], including demographical trends [21,28]. Moreover, monochromacy was not discussed in this work because of its rarity [24] but likely has an even more pronounced effect on colour discriminability than the deficiencies investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…Protan and deutan are the most common, affecting for example up to 9% of men and 0.6% of women in Europe, as well as 7% of men and 2% of women in China [21]. The prevalence of tritan in the West is on the order of 1:10 000 [25], though higher prevalences have been reported in other locations [28].…”
Section: Introductionmentioning
confidence: 99%
“…20 Similarly, a study carried out in Iran reported that prevalence of colour vision deficiency was higher in males than females. 21 Stereopsis, the ability to visualise objects in three dimensions, increases rapidly from the age of 4-7 years. 22 Severe visual impairment in children worsens their stereo acuity more than mild visual impairment.…”
Section: Aimmentioning
confidence: 99%
“…Color Vision Deficiency is found in 4.7% of Irani population. 3 In United Kingdom the prevalence is 6.7%, 8.5% in Mediterranean Croatia and 8.9% in Croatia. 3 The rate of dichromacy was higher in Mediterranean Croatia (2.40%), while the rate of anomalous trichromacy was greater in inland Croatia (6.93%).…”
Section: Introductionmentioning
confidence: 99%
“…3 In United Kingdom the prevalence is 6.7%, 8.5% in Mediterranean Croatia and 8.9% in Croatia. 3 The rate of dichromacy was higher in Mediterranean Croatia (2.40%), while the rate of anomalous trichromacy was greater in inland Croatia (6.93%). 4 A higher number of color vision deficiency is found in Australia and Turkey which is 7.4% and 7.3% respectively.…”
Section: Introductionmentioning
confidence: 99%